Diverse response of paramagnetic and ferromagnetic minerals to deformation from Intra-Carpathian Palaeogene sedimentary rocks: Comparison of magnetic susceptibility and magnetic remanence anisotropies. (August 2018) - Hrouda, František; Gilder, Stuart; Wack, Michael; Ježek, Josef
Abstract: All the minerals in a rock contribute to its anisotropy of magnetic susceptibility (AMS). In weakly magnetic sedimentary rocks, the strongest contributors are the paramagnetic minerals, predominantly represented by clay minerals, together with the ferrimagnetic minerals that are typically magnetite and/or maghemite. In contrast, ferrimagnetic minerals solely control the anisotropy of magnetic remanence (AMR). An investigation of both AMS and AMR can therefore help distinguish among the deposition, diagenetic and deformation histories of the paramagnetic and ferrimagnetic minerals in the same rock specimen. We present a test case from relatively weakly deformed Intra-Carpathian Palaeogene sandstones (Skorušina Hills, Slovak Republic) where AMR and AMS fabrics generally coaxial yet also exhibited notable differences. In particular, AMR foliations were more readily deflected away from the bedding plane, perpendicular to the maximum stress axis, than the AMS foliations. These factors are interpreted in terms of higher sensitivity of the ferrimagnetic minerals to ductile deformation than that of the paramagnetic clay minerals. Highlights: Anisotropies of magnetic susceptibility and magnetic remanence. Diverse responses of paramagnetic and ferromagnetic minerals to ductile deformation. Intra-Carpathian Palaeogene.